2007
DOI: 10.1016/j.mycres.2006.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Polyphyly and two emerging lineages in the rust genera Puccinia and Uromyces

Abstract: The phylogenetic validity of Puccinia and Uromyces, Pucciniaceae, and closely related genera was evaluated using nucLSU rDNA sequences. Using a wide range of rust species with different life cycles and with different host specificities, Puccinia and Uromyces were shown to be highly polyphyletic and to also include representatives of the genera Aecidium, Cumminsiella, Dietelia, Endophyllum, Miyagia, and Uredo. Furthermore, the structure of the phylogenetic data did not reflect previous sub-generic delimitations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 28 publications
(12 reference statements)
2
21
0
Order By: Relevance
“…Species infecting Cyperaceae or Juncaceae in their uredinial or telial state are found in a highly supported monophyletic group (group 1) among other angiosperm rusts. In contrast, species infecting Poaceae in their uredinial and telial stages are found in various unsupported clades outside group 1 and are referred to as group 2 (Aime 2006; Maier et al 2007). This study found that, although the sugarcaneinfecting Puccinia species are not closely related to each other, they both fall outside the highly supported group 1 rust clade, further maintaining the separation of rust species infecting Poaceae from Cyperaceae-and Juncaceae-infecting rusts and their evolutionary derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Species infecting Cyperaceae or Juncaceae in their uredinial or telial state are found in a highly supported monophyletic group (group 1) among other angiosperm rusts. In contrast, species infecting Poaceae in their uredinial and telial stages are found in various unsupported clades outside group 1 and are referred to as group 2 (Aime 2006; Maier et al 2007). This study found that, although the sugarcaneinfecting Puccinia species are not closely related to each other, they both fall outside the highly supported group 1 rust clade, further maintaining the separation of rust species infecting Poaceae from Cyperaceae-and Juncaceae-infecting rusts and their evolutionary derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale systematic studies of rust fungi have focused mainly on the SSU and LSU regions of rDNA (Aime 2006;Beenken et al 2012;Dixon et al 2010;Maier et al 2003Maier et al , 2007Minnis et al 2012;Wingfield et al 2004;Yun et al 2011) (Table 21). Protein coding genes such as beta-tubulin ; Van der Merwe et al 2007 and elongation factor (TEF) (Seier et al 2009; Van der Merwe et al 2007) were successfully used at the family, genus and species level in rust fungi, although beta-tubulin required cloning rather than direct sequencing of PCR product.…”
Section: Molecular Phylogenymentioning
confidence: 99%
“…Uromyces with one-celled teliospores is typically differentiated from Puccinia, although some species of Puccinia have both onecelled (mesospores) and two-celled teliospores, e.g., P. lagenophorae. Teliospore morphology is homoplasious, and Puccinia and Uromyces were polyphyletic in systematic studies based on the LSU and SSU regions of nuclear ribosomal DNA (Maier et al 2007;Aime 2006), and the two nuclear genes: elongation factor and β-tubulin ( Van der Merwe et al 2007). Some rust fungi have teliospores morphologically similar to Puccinia, but are not closely related or have an uncertain systematic position.…”
Section: Introductionmentioning
confidence: 99%
“…While these two genera form a strongly supported group together with two more genera, the analysis by Maier and coworkers (2003) also suggests that these two genera are polyphyletic. This pioneering work on molecular phylogeny of rust fungi has lately been substantiated by two further molecular studies (Maier et al 2007;van der Merwe et al 2007). Findings from these studies indicate that some of the morphological characteristics, i.e.…”
Section: Phylogeny and Taxonomymentioning
confidence: 96%
“…In terms of number of species the Pucciniaceae are by far the largest among all rust families (Maier et al 2007). Within this family, the genus Puccinia, with about 4000 species, and the genus Uromyces, with about 600 species, together represent almost two-thirds of all known rust species (Cummins and Hiratsuka 2003).…”
Section: Phylogeny and Taxonomymentioning
confidence: 99%